The Hyperledger fabric as a Blockchain framework preserves the security of electronic health records - Hasnain, Muhammad; Albogamy, Fahad R.; Alamri, Saeed S.; Ghani, Imran; Mehboob, Bilal (Frontiers in Public Health, 2023)
The Hyperledger fabric Fabric (HF) framework is widely studied for securing electronic health records (EHRs) in healthcare sector. Despite the various cross domain blockchain technology (BCT) applications, little has beenis known about the role of HF framework in healthcare. The purpose of the systematic literature review (SLR) is to review the existing literature on the HF framework and its applications in healthcare. This SLR includes literature published between January 2015 and March 2023 in ACM digital library, IEEE Xplore, SCOPUS, Springer, PubMed, and Google Scholar databases. Following the inclusion and exclusion criteria, a total of 57 articles were emerged as eligible for this SLR. The HF framework was found to be useful in securing health records coming from Internet of Medical Things (IoMT) and many other devices. The main causes behind using the HF framework were identified as privacy and security, integrity, traceability and availability of health records. Additionally, storage issues of transactional data over the blockchain is reduced by the usage of HF framework. This SLR also highlights potential future research trends to ensure the high-level security of health records.